Preparation of new glass systems by the polymeric precursor method for dental applications - Bertolini, M. J.; Zaghete, M. A.; Gimenes, R.; de Souza, R. F.; Vaz, L. G. (Elsevier B.V., 2004)
Glass ionomer cements (GICs) are largely employed in Dentistry for several applications, such as luting cements for the attachment of crowns, bridges, and orthodontic brackets as well as restorative materials. The development of new glass systems is very important in Dentistry to improve of the mechanical properties and chemical stability. The aim of this study is the preparation of two glass systems containing niobium in their compositions for use as GICs. Glass systems based on the composition SiO2,Al2O3-Nb2O5-CaO were prepared by chemical route at 700degreesC. The XRD and DTA results confirmed that the prepared materials are glasses. The structures of the obtained glasses were compared to commercial material using FTIR, Al-27 and Si-29 MAS-NMR. The analysis of FTIR and MAS-NMR spectra indicated that the systems developed and commercial material are formed by SiO4 and AlO4 linked tetrahedra. These structures are essential to get the set time control and to have cements. These results encourage further applications of the experimental glasses in the formation of GICs. (C) 2004 Elsevier B.V. All rights reserved.